De decasségui a professor : reflexão de acadêmicos do curso de Pedagogia acordo Brasil/Japão acerca de suas trajetórias - Monteiro, Edenar Souza (2015)
This study, presented at the Institute of Education of the Federal University of Mato Grosso, belonging to the Research Line: School Organization, Training and Teaching Practices, aims to investigate the career of teachers/academics from the Faculty of Distance Education Brazil-Japan Agreement, who went to Japan in dekassegui condition and became teachers. The main data collection instruments were oral and written narratives. The sources of the narratives were Student Memories, Electronic Socioeconomic Questionnaire, Narrative Interview and TCC Records (Course Completion Assignment). The theoretical framework was anchored in the literature on: dekasségui Movement (Costa 2007, Sasaki, 2009, 2011); learning of teaching, teacher training, teacher knowledge (Tardif 1998, 2007; Pepper 1997, 2006; Marcelo Garcia, 1999, 2009, 2010; Mizukami, 2003, 2008; Nóvoa 1995, 2007, 2009) among others. In addition, on the use of narratives as a data collection instrument, Souza (2004, 2006) support was sough. Presenting the narratives of the teachers in the form of single or continuous text, serving a single main theme entitled "Professional background: Higher education and knowledge required for the construction of teaching" was decided. The choice of continuous text also occurs because it deals about the subject’s trajectories that have gone through a professional transition. The narratives presented in this format allowed us to visualize the 'before' and 'after' the career of each teacher. Thus the results obtained revealed that the career path of these teachers underwent a transition and for family reasons they were inserted at school. When it realized teachers, they viewed the need for professional qualifications. In this scenario there is the opportunity to study pedagogy and in contact with during the learning stage, the theory during the training and the exchange of knowledge with classmates, built significant elements that resulted in the teacher education by strengthening the significance of what to be a teacher. In summary it can be said that these paths had elements that resulted in the meaning of what a teaching for these teachers.